Cell-free DNA as an obesity biomarker - Camuzi Zovico, P V; Gasparini Neto, V H; Venâncio, F A; Soares Miguel, G P; Graça Pedrosa, R; Kenji Haraguchi, F; Barauna, V G (Physiological research, 2020)
Obesity is a disease that affects about 13 % of the world population (2016) (Who 2018). This condition generates a process of systemic inflammation that may contribute to the release of cell-free DNA (cfDNA) into the bloodstream. cfDNA has been considered a potential biomarker to monitor several physiological and pathological conditions, such as tumors, exercise intensity and obesity. Therefore, the objective of this study was to evaluate the association of cfDNA levels with the amount of weight and fat mass lost six months after bariatric surgery. Thirty-eight subjects classified as obese (BMI, 43.5+/-6.2; BFP, 46.6+/-4.8) were evaluated anthropometrically and underwent bariatric surgery. Weight, BMI, body fat percentage (BFP), waist circumference, C-Reactive Protein (CRP) and cfDNA levels were evaluated before and six months after surgery; furthermore, a correlation was performed between cfDNA levels and BFP and CRP. Decrease in total body weight and CRP were observed after bariatric surgery; however, the cfDNA levels remained unchanged. There was a weak correlation between cfDNA levels and BFP before the bariatric surgery, and a moderate correlation between cfDNA and CRP. Obese subjects who underwent bariatric surgery, the decrease in body fat percentage did not result in changes in cfDNA levels six months after surgery.
Keywords: C-Reactive Protein; Obesity; C-reaktivní protein; Middle Aged; mužské pohlaví; Adult; bariatrická chirurgie; ženské pohlaví; Anthropometry; Humans; biologické markery; Cell-Free Nucleic Acids; lidé středního věku; volné cirkulující nukleové kyseliny; antropometrie; obezita; Bariatric Surgery; dospělí; Biomarkers; Female; lidé; Male